(untitled) (Perner’s Contacts, 2009)
The paper deals with influence of transport infrastructure into modal split on terminals of intermodal transport. This transport infrastructure of rail, road and water ist wery important for the modal split in terminals. The differences among transport infrastructure are described in this article.